A quantitative and qualitative method to control chemotherapeutic preparations by Fourier transform infrared–ultraviolet spectrophotometry. (June 2013) - Dziopa, Florian; Galy, Guillaume; Bauler, Stephanie; Vincent, Benoit; Crochon, Sarah; Tall, Mamadou Lamine; Pirot, Fabrice; Pivot, Christine
Chemotherapy products in hospitals include a reconstitution step of manufactured drugs providing an adapted dosage to each patient. The administration of highly iatrogenic drugs raises the question of patients' safety and treatment efficiency. In order to reduce administration errors due to faulty preparations, we introduced a new qualitative and quantitative routine control based on Fourier Transform Infrared (FTIR) and UV-Visible spectrophotometry. This automated method enabled fast and specific control for 14 anticancer drugs. A 1.2 mL sample was used to assay and identify each preparation in less than 90 sec. Over a two-year period, 9370 controlled infusion bags showed a 1.49% nonconformity rate, under 15% tolerance from the theoretical concentration and 96% minimum identification matching factor. This study evaluated the reliability of the control process, as well as its accordance to chemotherapy deliverance requirements. Thus, corrective measures were defined to improve the control process.